PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DINAS KEHUTANAN DAN PERKEBUNAN KABUPATEN SRAGEN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI - Rahayu Triastity, Agung Prasetyo & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2017)
The purpose of this study was to analyze the significance of theinfluence of the work environment, compensation and job satisfaction onperformance and job satisfaction on the moderation of the influence of theworking environment and compensation to performance.This study tookplace in the Forestry and Plantation Sragen with variables research ofworking environment, compensation, job satisfaction and performance. Thepopulation in this study were all employees in the Department of Forestry andPlantation in the Sragen regency totaling 38 employees. The collecting datain this study was using a questionnaire. The data analysis technique used totest the validity, reliability test, classic assumption test, and absolutedifference.The results of data analysis we concluded that: (1) The hypothesissaid that "the working environment have a significant effect on theperformance of staff at the Department of Forestry and Plantation Sragen"not verified, (2) The hypothesis said that "compensated significant effect onthe performance of staff at the Department of Forestry and PlantationSragen" was verified, (3) The hypothesis said that "the job satisfaction have asignificant effect on the performance of staff at the Department of Forestryand Plantation Sragen" was verified, (4) The hypothesis said that "jobsatisfaction moderate the influence of the working environment on theperformance of staff at the Department of Forestry and Plantation Sragen"was verified, (5) The hypothesis said that "job satisfaction moderatinginfluence compensation to the employee performance of Forestry andPlantation Sragen" not verified.Keywords: work environment, compensation, employee job satisfaction,performance.